2009
DOI: 10.1785/0120080217
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Weekly and Daily Earthquake Periodicities in the Western United States

Abstract: Analysis of apparent seismicity rate (ASR) using magnitude ≥ 1 earthquakes located in the western United States confirmed the existence of prominent spectral peaks with periods of 1 and 7 days. The number of recorded earthquakes on Sundays for the duration of 1963-2008 is about 5% higher than that on weekdays, and, more significantly, there is a 9% increase of ASR in the early morning compared with that in the middle of the days. Significant similarities in the spatial distributions of the weekly and daily var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 20 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Source processes that excite noise at these frequencies include anthropogenic activities [ Ringdal and Bungum , 1977; Gurrola et al , 1990; Young et al , 1996; Atef et al , 2009; Lewis and Gerstoft , 2012], wind acting on topographic irregularities [ Withers et al , 1996; Hillers and Ben ‐ Zion , 2011], precipitation and runoff [ Burtin et al , 2008], and thermoelastic straining [ Berger , 1975; Ben ‐ Zion and Leary , 1986; Hillers and Ben ‐ Zion , 2011]. Scattering and attenuation properties of the crustal material control the randomization of energy propagation directions and relative mode excitation [ Margerin et al , 1998, 2001; Larose et al , 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Source processes that excite noise at these frequencies include anthropogenic activities [ Ringdal and Bungum , 1977; Gurrola et al , 1990; Young et al , 1996; Atef et al , 2009; Lewis and Gerstoft , 2012], wind acting on topographic irregularities [ Withers et al , 1996; Hillers and Ben ‐ Zion , 2011], precipitation and runoff [ Burtin et al , 2008], and thermoelastic straining [ Berger , 1975; Ben ‐ Zion and Leary , 1986; Hillers and Ben ‐ Zion , 2011]. Scattering and attenuation properties of the crustal material control the randomization of energy propagation directions and relative mode excitation [ Margerin et al , 1998, 2001; Larose et al , 2008].…”
Section: Introductionmentioning
confidence: 99%
“…This is also supported by the existence of clear signals in both horizontal and vertical components (Figs 3 and S1). Changes in earthquake activity may also produce seasonal variations of noise, but apparent variations of seismicity have been associated with changes in network sensitivity (Atef et al 2009), which may result in part from seasonal noise as demonstrated by our analysis.…”
Section: Discussionmentioning
confidence: 63%
“…Energies at frequencies above 1 Hz are usually attributed to cultural noise, which propagates mainly as rapidly‐attenuating high‐frequency surface waves, manifested by significantly reduced noise amplitudes in boreholes (Gurrola et al 1990), tunnels, and mines. Diurnal and weekly variations of cultural noise (Ringdal & Bungum 1977) affect earthquake detection capabilities (Atef et al 2009). Wind acting on topographic irregularities or trees and posts can also transmit energy into the ground at high frequencies and the associated ground tilting may produce longer period noise.…”
Section: Introductionmentioning
confidence: 99%
“…These plots also show a short recovery of the detection capability around noon. [28] has found a similar pattern of the detection capability in California through the hourly distribution of the number of reported earthquakes in the Advanced National Seismic Systems (ANSS) catalogue. Note that, however, both magnitude-time plots and hourly distributions provides us with only a qualitative pattern of the detection capability.…”
Section: Discussionmentioning
confidence: 69%
“…In this chapter we considered only the daily variation of detection capability, but human activities also have a weekly periodicity [28]. Additionally, we often observe seasonal (annual) variations in seismic noise level [39,40], which are mainly caused by meteorological factors.…”
Section: Discussionmentioning
confidence: 99%